2020
DOI: 10.1038/s41467-020-19094-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells

Abstract: Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 36 publications
(45 reference statements)
4
43
1
1
Order By: Relevance
“…32,34,35 Interestingly, the loss of CD16 expression on NK cells by cryopreservation/thawing of human PBMCs has been reported in previous studies. 14,34,36 In the current study, the uCD56 dim NK-cell population was prominently observed in cryopreserved PBMCs from patients with COVID-19, but not healthy donors, indicating that NK cells become abnormally labile to ex vivo cellular stress, such as cryopreservation/thawing, during COVID-19. In the present study, we also showed that the frequency of CD62L 1 cells was significantly lower among uCD56 dim NK cells than among cCD56 dim NK cells (Fig E10 ), indicating that the ADAM17 activity is increased in uCD56 dim NK cells.…”
Section: Discussionmentioning
confidence: 50%
“…32,34,35 Interestingly, the loss of CD16 expression on NK cells by cryopreservation/thawing of human PBMCs has been reported in previous studies. 14,34,36 In the current study, the uCD56 dim NK-cell population was prominently observed in cryopreserved PBMCs from patients with COVID-19, but not healthy donors, indicating that NK cells become abnormally labile to ex vivo cellular stress, such as cryopreservation/thawing, during COVID-19. In the present study, we also showed that the frequency of CD62L 1 cells was significantly lower among uCD56 dim NK cells than among cCD56 dim NK cells (Fig E10 ), indicating that the ADAM17 activity is increased in uCD56 dim NK cells.…”
Section: Discussionmentioning
confidence: 50%
“…Our ultimate goal is to deploy this manufacturing pipeline for clinical use, requiring cryopreservation and banking of manufactured CAR-NK cells. Recent studies have shown that while cryopreservation may have little effect on NK viability, it can cause a loss of cytotoxic function 55 . Thus, we tested cytotoxicity of CAR-NK cells immediately after thaw or after overnight culture in media containing 100 IU/mL IL2 (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…CAR-NK cells showed high levels of degranulation, inflammatory cytokine production, and target cell killing compared to CAR-negative controls (Figure 3A – 3D). Interestingly, it has been shown that cryopreservation may lead to reduced cytotoxicity of NK cells 55 . An off-the-shelf product requires cryopreservation and banking of engineered cells.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments are based on natural killer (NK) cells from human donors, which are in vitro activated and expanded 16 . A number of 300.000 NK immune cells and 120.000 K562 tumor cells are mixed with ice-cold 1500 µ l acid-dissolved collagen solution (1.2 mg/ml) and pipetted in each well of a tissue-culture treated 6-well plate (Corning).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, cells are segmented from the background and classified with a convolutional neural network, using the same method as described in 16 . The network has been trained on 6 manually labeled minimum/maximum intensity projection images of NK cells, mixed with K562 cells.…”
Section: Methodsmentioning
confidence: 99%